Transmission electron microscopic study of the long period modulated phase in the morphotropic phase-boundary region of (1-x) NaNbO3 -xCaTiO3 for x=0.16 - Tripathi S.; Lalla N.P.; Pandey D. (My University, 2025)
The recently reported structure of the long period modulated phase of (1-x) NaNb O3 -xCaTi O3, with x=0.16, has been revisited using transmission electron microscopic studies. It is shown that the dominant phase in the morphotropic phase boundary region of this mixed system is incommensurately modulated in the [001] direction with an approximate unit cell size of 2 ap ×2 ap ×24 ap, where ap is the pseudoperovskite cell parameter. © 2008 American Institute of Physics.